Estimasi Biaya Alat Muat Dan Angkut Penambangan Quarry Batu Andesit PT Putra Elan Balindo Pada Kota Palu Sulawesi Tengah - Indri Tenri Datu; Henny Magdalena; Windhu Nugroho; Lucia Litha Respati; Harjuni Hasan (Fakultas Teknik Universitas Cenderawasih, 2023)
PT. Putra Elan Balindo is a company engaged in the mining sector specially the andesite minerals domiciled in Palu City. PT. Putra Elan Balindo located in Watusampu Village, Ulujadi District, Palu City, Central Sulawesi, which has an IUP (Mining Business Permit) with an area of 17.89 Ha. To achieve production targets set by the company using a combination of tools mechanics in the form of Excavator Komatsu PC 400 and Dump Truck Hino FM 260 JD, where there is currently only 1 Excavator while the Dump Truck is 2 are needed with a production target of 20,000 m3 per month and have 1 shift working hours. Based on the results of research carried out for one month, it shows that the productivity of the Komatsu PC 400 Excavator is 174.29 m3 / hour and the Hino FM 260 JD Dump Truck is 197.69 m3 / hour for 2 transport equipment. The cost of owning a Hino FM 260 JD Dump Truck is Rp. 476,190/hour and the cost of owning a Komatsu PC 400 Excavator is Rp. 267,857/hour while operational costs for the Hino FM 260 JD Dump Truck are Rp. 1,862,072/ hour and operational costs for a Komatsu PC 400 Excavator Rp. 2,135,421/hour.